Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.21037/gs.2019.05.01
|View full text |Cite
|
Sign up to set email alerts
|

BI-RADS 4 breast lesions: could multi-mode ultrasound be helpful for their diagnosis?

Abstract: Background: The malignant probability of Breast Imaging Reporting and Data System (BI-RADS) 4 breast lesions is 3-94%, which is a very large span, and thus leads to a high rate of unnecessary biopsy. Therefore, the differential diagnosis of benign and malignant BI-RADS 4 breast lesions has become extremely important. Thus, in this paper, we investigated the diagnostic value of conventional ultrasonography (US), contrast-enhanced ultrasound (CEUS) and shear wave elastography (SWE) for BI-RADS 4 breast lesions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 31 publications
(33 reference statements)
5
31
3
Order By: Relevance
“…SWE could quantitatively evaluate the elastic characteristics of breast lesions and more accurately judge the benign and malignant breast lesions. Our study showed that there were signi cant differences in elastic characteristics between benign and malignant breast lesions, which were the same as those of previous studies [8,20]. For malignant breast lesions, a large number of cancer cells proliferated, invaded and in ltrated the normal breast stroma and adipose tissue, and interacted with the tumor microenvironment, causing complex connective tissue hyperplasia and brosis, which were important typical pathological changes in the process of tumor development and invasion, they could lead to overexpression and accumulation of ECM components, rearrangement and cross-linking of ECM structure [21,22], and increase the stiffness of the lesions.…”
Section: Discussionsupporting
confidence: 91%
“…SWE could quantitatively evaluate the elastic characteristics of breast lesions and more accurately judge the benign and malignant breast lesions. Our study showed that there were signi cant differences in elastic characteristics between benign and malignant breast lesions, which were the same as those of previous studies [8,20]. For malignant breast lesions, a large number of cancer cells proliferated, invaded and in ltrated the normal breast stroma and adipose tissue, and interacted with the tumor microenvironment, causing complex connective tissue hyperplasia and brosis, which were important typical pathological changes in the process of tumor development and invasion, they could lead to overexpression and accumulation of ECM components, rearrangement and cross-linking of ECM structure [21,22], and increase the stiffness of the lesions.…”
Section: Discussionsupporting
confidence: 91%
“…A previous study has con rmed that multi-mode US (US combined with CEUS, SWE) can signi cantly improve the diagnostic e cacy of breast cancer [8]. Similarly, another study has con rmed that CEUS combined with SWE can greatly improve the detection rate of small breast cancer [9].…”
Section: Introductionmentioning
confidence: 97%
“…In addition, lymphangiography revealed decrease in the lymphatic sinus region due to the tumor formation at the early stage of metastasis, i.e., the parenchyma was replaced with tumor cells 25 . Therefore, a perfusion defect in a metastatic LN at an early stage is presumed to be an event that is distinct from those associated with hypoxia, angiogenesis, keratinization and tissue necrosis, which occur as tumor growth rapidly progresses 26,27 . The present study aims to elucidate the mechanisms of perfusion defect formation in the tumor mass in the nonenlarged LN at the early stage of metastasis.…”
Section: Introductionmentioning
confidence: 99%